Knowledge and Quality of Life in Type 2 Diabetes Mellitus Patients and its Related Factors - Agustina Nila Yuliawati; Pande Made Desy Ratnasari; Putri Riski Rosalina (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Knowledge is important to control blood sugar and prevent complications, and subsequently have an impact on the quality of life (QOL) of type 2 diabetes mellitus (T2DM) patients as a response to their health. This study was aimed to determine the correlation between the level of knowledge and QOL in type 2 DM (T2DM) patients, as well as its related factors. This cross-sectional study was conducted in a Public Hospitals, Buleleng, Bali on September 2020. The inclusion criteria included T2DM outpatients aged ≥ 18-year-old, getting similar therapy for at least 3 months, filling out the questionnaire completely, being able to communicate well, and not in a pregnant/breastfeeding condition. Data were obtained by medical records, questionnaires DKQ-24 (knowledge) and EQ-5D-5L (QOL). The correlation between knowledge and QOL of T2DM patients and its related factors were analyzed using bivariate statistical tests. The findings of the 150 respondents showed that the majority of the patients were ≥ 60-year-old (53.3%), female (50.7%), first educational level (64%), not working (54%), low income (49.3%), >5 years of T2DM duration (44%), no complications (75.3%), taking 4-6 item medicines (66.7%), moderate knowledge level (70.7%) with QOL based on the utility score 0.892±0.154 and VAS 59.73±20.07. Statistical tests showed there was a significant correlation between knowledge and QOL based on utility value (p=0.01), but not with VAS value (p=0.165). These was reinforced by age which has a significant correlation with knowledge (p=0.042), also employment status and complications condition which have a significant correlation with QOL (p<0.05). Patients with a higher level of knowledge have a better QOL, despite different backgrounds.